2011
DOI: 10.1002/jcp.22601
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of gastrokine 1 in gastric cancer cells induces Fas‐mediated apoptosis

Abstract: Gastrokine 1 (GKN1) is involved in the replenishment of the surface lumen epithelial cell layer, in maintaining the mucosal integrity, and could play a role in cell proliferation and differentiation. In fact, after injury of the gastric mucosa, restoration may occur very rapidly in the presence of GKN1. In contrast, if the protein is downregulated, the repair process may be hampered; however, application of GKN1 to gastrointestinal cells promoted epithelial restoration. Because GKN1 possesses some mitogenic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
8
38
0
Order By: Relevance
“…After transfection, cell growth and apoptosis was evaluated by cytofluorimetry. The overexpression of GKN1 in MKN28 or AGS cells, with respect to control cells, reduced cell growth (Rippa et al, 2010). A similar effect was also reported by Shiozaki et al, 2001, who observed a reduction in MKN28 colony formation in cells transfected with CA11 gene with respect to control cells.…”
Section: Evaluation Of Transient Expression Of Gkn1 In Gastric Cancersupporting
confidence: 84%
“…After transfection, cell growth and apoptosis was evaluated by cytofluorimetry. The overexpression of GKN1 in MKN28 or AGS cells, with respect to control cells, reduced cell growth (Rippa et al, 2010). A similar effect was also reported by Shiozaki et al, 2001, who observed a reduction in MKN28 colony formation in cells transfected with CA11 gene with respect to control cells.…”
Section: Evaluation Of Transient Expression Of Gkn1 In Gastric Cancersupporting
confidence: 84%
“…GKN1 connected with decreasing the formation of colonies and proliferation by an atypical glandular cell of gastric mucosa and reducing of cellular viability, proliferation, and colony . GKNs and trefoil factors (TFFs) both are together lead to enhance cellular differentiation, cytoprotective role and working on NF-κβ signalling pathways that result anti-inflammatory effects, therefore it promotes restoration of gastric epithelial cells (Rippa et al, 2011). If any change on the expression of GKN gene cause deficiency of GKN1 & GKN2, results from gastric inflammation, non-steroidal antiinflammatory (NSAID) induced mucosal injury and the development of neoplasia of gastric mucosa Nardone et al, 2008).…”
Section: Etiopathogenesis Of Gastritis and Peptic Ulcer Diseasesmentioning
confidence: 99%
“…Resveratrol, a compound found in grapes and red wine inhibits EMT in lung cancer [127] similarly to Celastrol, also known as tripterine, that also has inhibitory effects [128]. In the early stages of gastric neoplastic transformation the overexpression of gastrokine 1 might protect against MET [129]. The use of anti-HER2 drugs is promising but apparently only in HER2-positive gastric cancer [130].…”
Section: Clinical Implications Of Claudins Emt and Inflammationmentioning
confidence: 99%